Time of year and fungicides on anthracnose intensity in bananas from Northern Minas Gerais - Fernandes, Martielle Batista; Castro, Sabrina Gonçalves Vieira de; Sousa, Irisléia Pereira Soares de; Moura, Marielly Maria de Almeida; Matos, Amanda Dayanne Malta; Almeida, Luciele Barboza de; Santos, Michelle de Oliveira; Dias, Wlly Polliana Antunes; Mizobutsi, Gisele Polete; Mizobutsi, Edson Hiydu (Seven Editora, 2024)
Banana cultivation is an important economic activity in the semi-arid region of Minas Gerais, however, diseases such as anthracnose are responsible for great losses that affect this fruit. The objective of this study was to evaluate the time of year and the effect of fungicides recorded on anthracnose intensity in the postharvest of ’Prata-Anã’ banana produced in the North of Minas Gerais. The study was carried out from February 2017 to January 2018, with bunches of ’Prata-Anã’ banana collected monthly. The central bunches were transported to the laboratory and subdivided into bouquets of three fruits. The fruits were treated with fungicides registered for the crop: imazalil and thiabendazole, immersed for two minutes at the recommended concentrations of 2 mL.L-1 and 0.92 mL.L-1, respectively, throughout the year. The fruits immersed for two minutes in water were the control treatment. Disease intensity was assessed by the severity of anthracnose in the fruits and the area under the disease severity progress curve (AACPS) in the fruits was calculated. The experimental design was completely randomized, consisting of three treatments, twelve evaluation periods, five replications and three fruits per replication. The data were submitted to analysis of variance and the means were compared using the Scott-Knott test (p<0.05). The fungicide thiabendazole was inefficient for the control of anthracnose in the postharvest of ’Prata-Anã’ banana. The distribution of rainfall interfered significantly with the development of anthracnose. Treatment with the fungicide imazalil showed the lowest AACPS values throughout the year. DOI:https://doi.org/10.56238/sevened2024.007-010